2021
DOI: 10.3390/ani11061482
|View full text |Cite|
|
Sign up to set email alerts
|

Physiological and Clinical Responses in Pigs in Relation to Plasma Concentrations during Anesthesia with Dexmedetomidine, Tiletamine, Zolazepam, and Butorphanol

Abstract: Reliable protocols for short-term anesthetics are essential to safeguard animal welfare during medical investigations. The aim of the study was to assess the adequacy and reliability of an anesthetic protocol and to evaluate physiological and clinical responses, in relation to the drug plasma concentrations, for pigs undergoing short-term anesthesia. A second aim was to see whether an intravenous dosage could prolong the anesthesia. The anesthesia was induced by an intramuscular injection of dexmedetomidine, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…[9][10][11][12] Although well-established protocols for shortterm anaesthesia exist, they often involve various combinations of opioids, benzodiazepines and alpha-2-agonists, which are associated with adverse effects such as obstipation, nausea, extended recovery, drug interactions or unwanted alterations in the animal's physiology that can interfere with the outcome of the study. [13][14][15] Therefore, the need for anaesthesia is a major limitation as it is not only stressful for the animal and increases procedural costs, but also limits the frequency of which urine specimens can be collected as daily anaesthesia for many days in a row is undesirable due to the concern for the animal's welfare. To avoid anaesthesia, we explored the approach of cleancatching midstream urine specimens from pigs, a sampling method which is similar to the one used in humans.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Although well-established protocols for shortterm anaesthesia exist, they often involve various combinations of opioids, benzodiazepines and alpha-2-agonists, which are associated with adverse effects such as obstipation, nausea, extended recovery, drug interactions or unwanted alterations in the animal's physiology that can interfere with the outcome of the study. [13][14][15] Therefore, the need for anaesthesia is a major limitation as it is not only stressful for the animal and increases procedural costs, but also limits the frequency of which urine specimens can be collected as daily anaesthesia for many days in a row is undesirable due to the concern for the animal's welfare. To avoid anaesthesia, we explored the approach of cleancatching midstream urine specimens from pigs, a sampling method which is similar to the one used in humans.…”
Section: Introductionmentioning
confidence: 99%
“…for transport or non-surgical interventions. Authors reported that hemodynamic variables were stable and breathing patterns were regular [ 15 , 16 ]. This is in accordance with the results presented here.…”
Section: Discussionmentioning
confidence: 99%
“…There were several errors in the original article [ 1 ]: In the sixth line of the abstract, instead of “The anesthesia was induced by an intramuscular injection of dexmedetomidine, tiletamine zolazepam, and butorphanol in 12 pigs”. It should be “The anesthesia was induced by an intramuscular injection of dexmedetomidine, tiletamine-zolazepam, and butorphanol in 12 pigs”.…”
mentioning
confidence: 99%